Propuesta de un sistema agroforestal como alternativa para la restauración de áreas deforestadas en la vereda naranjos del municipio de Gama, Cundinamarca. (2020)
The human being throughout history, has deteriorated ecosystems consuming the renewable and non-renewable resources of the natural environment, that is why we are looking for a way to stop and counteract the consequences that the deterioration of the soils entail. In this project, the different classes of agroforestry systems were identified, in order to find methods for a sustainable system in the territories damaged by agriculture and extensive cattle ranching. The project was carried out in three phases: The first was to search for bibliographies in reliable pages, where topics on new systems implemented over time, at the international and national levels, were found. In the second phase, an area was identified to make a diagnosis according to reliable sources from the mayor's office, corporations and territorial control entities, a survey was also carried out with farmers in some plots of the selected village, it was necessary to visit to observe and specify the diagnosis. Finally, according to the diagnosis carried out, a plot of the region was identified, to design an agroforestry system according to the characteristics of the soil and what was diagnosed in the population